2022
DOI: 10.1002/hsr2.504
|View full text |Cite
|
Sign up to set email alerts
|

Integrating healthcare for follow‐up of adult COVID‐19 patients in an outpatient clinic: A matter of cooperation

Abstract: Rationale, aims, and objectives A large number of patients infected with SARS‐CoV‐2 (COVID‐19) need outpatient follow‐up after hospitalization. As these patients may experience a broad range of symptoms, as do patients infected with the related SARS‐CoV‐1 virus, we set up a multidisciplinary outpatient clinic involving pulmonologists, internists, and geriatricians. Patients were allocated to a specialist based on symptoms reported on a self‐developed questionnaire of expected symptoms of COVID‐19. This study a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Seventeen articles discussed care models for treating people with PCC. [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Many health systems have begun developing care models to support people with PCC. A living systematic review examined evidence on care models and identified 4 main interfaces for care pathways: (1) coordination of referrals across care settings; (2) primary care teams to screen and support medical needs;…”
Section: Models Of Care For Treating People With Pccmentioning
confidence: 99%
“…Seventeen articles discussed care models for treating people with PCC. [80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] Many health systems have begun developing care models to support people with PCC. A living systematic review examined evidence on care models and identified 4 main interfaces for care pathways: (1) coordination of referrals across care settings; (2) primary care teams to screen and support medical needs;…”
Section: Models Of Care For Treating People With Pccmentioning
confidence: 99%